Treatment of heart failure after myocardial infarction with bone marrow-derived mesenchymal stem cells - Hong Yu; Kai Lu; Jianan Wang (Cardiology Plus, 2016)
Heart failure (HF) after myocardial infarction (MI) represents a worldwide public health issue with gradually increasing incidence. HF may eventually affect all organs and tissues and is associated with significant morbidity and mortality. Current therapeutic methods to treat HF stay at only delaying the disease progression without repair and regeneration. Recently, cell transplantation has gradually become the most promising treatment for the damaged myocardial tissue. Meanwhile, the bone marrow-derived mesenchymal stem cells (MSCs) are the most used cells for the treatment of HF. In the present review, we summarize the current literature on MSCs and their potential use to treat HF after MI. So far, MSCs have been demonstrated beneficial competence in animal studies and clinical trials, which may open novel avenues for further clinical studies.